A cross-sectional survey of clinical factors that influence the use of traditional Korean medicine among children with cerebral palsy - Hye-Yoon Lee; Young-Ju Yun; Sun-Ae Yu; Yo-Han Park; Byung-Wook Park; Bu-Young Kim; Man-Suk Hwang (Integrative Medicine Research)
Background: Traditional Korean medicine (TKM) is widely used to treat children with cerebral palsy (CP) in Korea; however, studies investigating factors that influence the use of TKM are scarce. Thus, we investigated the clinical factors that might influence the use of TKM. Methods: A population-based, cross-sectional, multicenter survey was performed from August 2014 to May 2016. The history of TKM use, type and severity of CP, current treatment characteristics, presence of accompanying disabilities or other health problems not directly related to CP, and monthly cost for the treatment of CP were surveyed. Results: In total, 182 children were recruited, and 78 children (42.9%) had used TKM. Among these 78 children, 50 (64.1% of the TKM-use group) had used both acupuncture and herbal medication, 15 (19.2%) had used acupuncture only, and 13 (16.7%) had used herbal medication only. Children with non-typical CP, accompanying disabilities and general health problems tended to use TKM. The monthly cost of treatment for CP was significantly higher in the TKM-use group than that in the no-TKM-use group, suggesting that economically disadvantaged children may have difficulty in accessing TKM. Dietary supplements, conventional pharmacological treatments, and rehabilitation therapies did not affect TKM use. Conclusion: Children with non-typical symptoms or those with poor overall health status are likely to use TKM. Additionally, TKM use leads to increased treatment costs. Studies investigating the motivation for starting or ceasing TKM therapy, socioeconomic factors and the attitude of parents towards complementary and alternative medicine should be performed. Keywords: Cerebral palsy (CP), Children with CP, Acupuncture, Herbal medication, Traditional Korean medicine (TKM)